Biodegradable Microparticles with Surface Dimples as a Bi‐Modal Imaging Contrast Agent. Issue 5 (25th January 2013) - Kim, Mi Ri; Lim, Yong Taik; Cho, Kuk Young
Abstract Fabrication of physically engineered colloids and their application to the biological fields is emerging importance because of their potential to provide an enhanced performance without altering the chemical properties of biomaterials used. A facile approach is reported to fabricate sub‐10‐μm‐sized PLGA microparticle with small dimples covering the surface by droplet imprinting. Optical and magnetic resonance bioimaging agents are easily co‐encapsulated inside the microparticles to obtain a bi‐modal imaging agent. Cell internalization efficacy of dimpled particles in DC 2.4 cell is enhanced compared with conventional smooth round‐shaped colloids. Our result indicates that morphology‐controlled microparticles show promise as a cell labeling with improved cell interaction.